INTRODUÇÃO À ARQUITETURA - DA PRÁTICA PARA A TE0RIA - HAMMARSTRON, ADRIANE W.; ZARTH, ANTÔNIO M. F.; LINDORFER, CARINE; PEREIRA, TÂNIA M.; ALCÂNTARA, ROMÁRIO L.; AMMAR, MARWAN; PEREIRA, JULIANE S. (Salão do Conhecimento, 2013)
Resumo